Factors contributing to the variation of the fearful withdrawal response to humans in minipigs bred at ICG SB R - V. S. Lankin; S. V. Nikitin; O. V. Trapezov (Вавиловский журнал генетики и селекции)
The fearful withdrawal response to humans was studied with regard to the effect of hereditary and environmental factors in four consecutive generations of minipigs bred at the Institute of Cytology and Genetics. Variation in the withdrawal response was tested in four heterotypic settings. The standard aversive stimulus was the presence of a human as the animals were being given food either as a group or one by one after 14–16 or 2 h of food deprivation. All factors studied are ranged with regard to their contributions to the overall phenotypic variation of the response as follows: sex (0.0–0.4 %), age (0.1–4.7 %), social isolation (0.1–2.1 %), colour types (2.9–7.8 %), boar genotype (10.8 %), food motivation (6.1–12.8 %), and the genotype–food motivation interaction (2.7–56.4 %). That was the first demonstration of hereditary polymorphism of this behavioral reaction in minipigs, which includes three classes of behavioral phenotypes. Sex and age do not affect the withdrawal response in piglets from 1.5-month age to 4.1-month age. It was found that the age-related changes in the behavior of sows depend on the indirect selection of individuals with a quiet phenotype, and the frequency of this phenotype increases from 29 % (the rearing stock) to 63 %. Social isolation and food motivation significantly influence the response in piglets at ages of 1.5 and 4.1 months, but not in sows at ages of 10.4 and 22.5 months. An adverse consequence of the environmental influence of food motivation and its interaction is a broad variability (CV 95–120 %) of the withdrawal response. The results will contribute to the study of the genetics of the fearful-defensive response to humans and to correction of the method for evaluating this behavior, valuable for breeding, in ICG minipigs.